Unveiling the cytotoxic and apoptosis-inducing abilities of an edible bird’s nest extract in human hepatocellular carcinoma Huh-7 cells - Nguyen, Thi-Phuong; Duong, Tang Van; Do, Hoang Dang Khoa; Le, Van Minh; Ta, Kim Nhung; Nguyen, Khoa Thi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Edible bird’s nest (EBN) is renowned for diverse pharmacological properties; however, its ability to cause cancer cell death has not been found in recent studies. This study investigates the phytochemical composition of EBN ethanol extract (EEE), the cytotoxic and apoptosis-inducing effects of the extract on human hepatocellular carcinoma Huh-7 cells. Qualitative and quantitative tests showed that proteins and peptides were abundant in the EEE. In the MTT assay, the extract exhibited cytotoxic activity against Huh-7 cells (IC50 = 58.57 ± 2.66 μg/mL, 53.15 ± 3.07 μg/mL, and 55.27 ± 1.85 μg/mL at 24 h, 48 h, and 72 h of incubation, respectively). Annexin-V/PI staining suggested that the extract provoked apoptosis in Huh-7 cells by deregulating the expression patterns of apoptotic markers including caspase 3, caspase 8, caspase 9, and survivin. These findings demonstrate the potential of the EEE as a promising anticancer candidate for further studies.